Sustainable Tourism Development and Competitiveness: A Systematic Literature Review the Role of Artificial Intelligence in Destination Development - Ratih Pratiwi; Marno Nugroho (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Technology that is growing rapidly at this time supports the use of technology in the field of tourism development and competitiveness. The purpose of this literature research is to determine the role of Artificial Intelligence in the development of local tourism destinations. In addition, through this research, positive and negative impacts of the use of Artificial Intelligence in the development and competitiveness of sustainable tourism were obtained. The positive impact is the ease of reaching tourism locations, the ease of knowing about the tourism to be visited, making it easier for visitors to find out prices and facilities in tourism destinations, increasing the economy of residents in the local area and increasing national income. In addition, the use of Artificial Intelligence in the development and competitiveness of sustainable tourism also has a negative impact, namely, there are several jobs that are replaced by artificial intelligence. This can be detrimental to some parties but should be given a solution by providing training on.